AN EVENT AT THE DAWN OF MODERN KOREAN POETRY: KIM SOWOL’S “AZALEAS” - JEONG, Myeong Kyo (International Journal of Korean Humanities and Social Sciences, 2019)
Kim Sowol is one of the Korean poets who opened the horizon of modern poetry in Korea. His poem, “Azaleas”(1925) has been known as a masterpiece which Korean people love most to recite as “To Cassandra” of Pierre de Ronsard in France. Nevertheless, this poem has been taken for the highest expression of the traditional sentiment without being appreciated for the quality of the modern poetry as follows: Koreans have sung for a long time the sorrow from the parting with the lover. In “Azaleas”, any reader can see easily the repeat of the same situation and same feeling. In this article I analyzed the attitude and the intention of the speaker of this poem and reinterpret the theme of poem. In doing so, I found the clever strategy of the speaker in front of the irreversible situation to press secretly the reflection of the lover about his departure. This strategy is the invention of the modern [wo]man which can appropriate the crisis. So, I defined the modern characteristic of this poem and proved that this poem is not a repeated expression of the traditional feeling of the Koreans, but the de/re-construction of that.